2021
DOI: 10.1016/j.jneb.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Community-Academic Partnerships to Promote Health Literacy and Address Social Needs Among Low-Income Families During COVID-19

Abstract: Brighter Bites is a school-based health promotion program that delivers fresh produce and nutrition education to low-income children and their families across six cities in the U.S. This paper provides a perspective on how, despite COVID-19-related school closures, Brighter Bites pivoted rapidly to collaborate with medical and public health institutions to improve health and food literacy among their families. Through these partnerships, Brighter Bites was able to rapidly provide accurate, evidence-based infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The current COVID-19 pandemic is a rapidly evolving global challenge and like any pandemic, it weakens health systems, costs lives, and also poses great risks to the global economy and security (Chattu et al, 2020 ). Socioeconomic disparities resulting from job losses and other systemic barriers can also exacerbate mental health issues (e.g., anxiety, depression, etc) among the general population amid COVID-19 (Haidar et al, 2020 ). As one of the most common insecurities, economic insecurity (EI) refers to the sense of uncertainty and unpredictability generated by individuals related to their economic status (Abeyta et al, 2016 ; Chou et al, 2016 ; Losee et al, 2020 ), including fear of unemployment, feeling that the economic situation may get worse, etc (Kopasker et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current COVID-19 pandemic is a rapidly evolving global challenge and like any pandemic, it weakens health systems, costs lives, and also poses great risks to the global economy and security (Chattu et al, 2020 ). Socioeconomic disparities resulting from job losses and other systemic barriers can also exacerbate mental health issues (e.g., anxiety, depression, etc) among the general population amid COVID-19 (Haidar et al, 2020 ). As one of the most common insecurities, economic insecurity (EI) refers to the sense of uncertainty and unpredictability generated by individuals related to their economic status (Abeyta et al, 2016 ; Chou et al, 2016 ; Losee et al, 2020 ), including fear of unemployment, feeling that the economic situation may get worse, etc (Kopasker et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, among Brighter Bites families, studies have demonstrated a 22% increase in food insecurity during the initial shelter-in-place phase of the pandemic (April-June 2020), with fear of COVID-19, unemployment, financial hardship, and food insecurity being the primary concerns among their participating families [25]. In response to this need, Brighter Bites pivoted rapidly to adopting a multi-pronged strategy of (a) increasing their health literacy portfolio [27]; (b) partnering with local food banks and other social service agencies to distribute produce at community sites, and also providing immediate response to families with urgent social needs [28]; (c) partnering with food growers to distribute produce boxes to families as part of the USDA farmers-to-families programing [29]; and (d) forming for-profit-retail partnerships as described in this paper. All strategies were deployed simultaneously in April 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Local Public Health Departments, in collaboration with hospital administrators and physicians, should engage nearby academic laboratories and work on formulating collaborations and agreements in preparation for future pandemics. Indeed, throughout the pandemic, several examples further highlight the utility of multi-sectoral and community collaborations for pandemic response [ 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%